The CANNA-TICS Study Protocol: A Randomized Multi-Center Double-Blind Placebo Controlled Trial to Demonstrate the Efficacy and Safety of Nabiximols in the Treatment of Adults With Chronic Tic Disorders - Jakubovski, Ewgeni; Pisarenko, Anna; Fremer, Carolin; Haas, Martina; May, Marcus; Schumacher, Carsten; Schindler, Christoph; Häckl, Sebastian; Aguirre Davila, Lukas; Koch, Armin; Brunnauer, Alexander; Cimpianu, Camelia Lucia; et al. (Frontiers in Psychiatry, 2020)
Background: Gilles de la Tourette syndrome (TS) is a chronic neuropsychiatric disorder characterized by motor and vocal tics. First-line treatments for tics are antipsychotics and tic-specific behavioral therapies. However, due to a lack of trained therapists and adverse events of antipsychotic medication many patients seek alternative treatment options including cannabis. Based on the favorable results obtained from case studies on different cannabis-based medicines as well as two small randomized controlled trials using delta-9-tetrahydrocannabinol (THC), we hypothesize that the cannabis extract nabiximols can be regarded as a promising new and safe treatment strategy in TS. Objective: To test in a double blind randomized clinical trial, whether treatment with the cannabis extract nabiximols is superior to placebo in patients with chronic tic disorders. Patients and Methods: This is a multicenter, randomized, double-blind, placebo controlled, parallel-group, phase IIIb trial, which aims to enroll 96 adult patients with chronic tic disorders (TS or chronic motor tic disorder) across 6 centers throughout Germany. Patients will be randomized with a 2:1 ratio into a nabiximols and a placebo arm. The primary efficacy endpoint is defined as tic reduction of at least 30% (compared to baseline) according to the Total Tic Score of the Yale Global Tic Severity Scale (YGTSS-TTS) after 13 weeks of treatment. In addition, several secondary endpoints will be assessed including changes in different psychiatric comorbidities, quality of life, driving ability, and safety assessments. Discussion: This will be the first large, controlled study investigating efficacy and safety of a cannabis-based medicine in patients with TS. Based on available data using different cannabis-based medicines, we expect not only a reduction of tics, but also an improvement of psychiatric comorbidities. If the cannabis extract nabiximols is proven to be safe and effective, it will be a valuable alternative treatment option. The results of this study will be of high health-economic relevance, because a substantial number of patients uses cannabis (illegally) as self-medication. Conclusion: The CANNA-TICS trial will clarify whether nabiximols is efficacious and safe in the treatment of patients with chronic tic disorders. This trial is registered at clinicaltrialsregister.eu (Eudra-CT 2016-000564-42) and clinicaltrials.gov (NCT03087201).